Estimatig the amount of potassium radiation effect on soil using Neville and Hermite numerical methods - Raad A. Hameed; Ghassan E. Arif; Aws A. Hamdi (Tikrit Journal of Pure Science, 2023)
The aim of this work is to estimate the effect of potassium radiation on soil in Nineveh governorate using some methods of numerical interpolation. We used (Neville, and Hermite) methods and obtained mathematical models by which we quantified the effect of radiation on soil in Nineveh governorate. The deductible results were very close to the real results. We then estimated the effect of potassium radiation on soil in Nineveh governorate outside the field measured areas.